Antimicrobial Peptide Analogs From Scorpions: Modifications and Structure-Activity - Amorim-Carmo, Bruno; Parente, Adriana M. S.; Souza, Eden S.; Silva-Junior, Arnóbio A.; Araújo, Renata M.; Fernandes-Pedrosa, Matheus F. (Frontiers in Molecular Biosciences, 2022)
The rapid development of multidrug resistant pathogens to conventional antibiotics is a global public health problem. The irrational use of antibiotics has promoted therapeutic limitations against different infections, being necessary research of new molecules to apply in infections treatment. Antimicrobial peptides (AMPs) are a new class of promising antibiotic molecules since they present broad action spectrum, potent activity and do not easily induce resistance. Several antimicrobial peptides from scorpion venoms have been described as potential source for the development of new drugs, however, some limitations to their application are also observed. Here we describe strategies used in several approaches to optimize scorpion antimicrobial peptides, addressing their primary sequence, biotechnological potential and characteristics that should be taken into account when developing a new antimicrobial molecule from scorpion peptides.